Assessment Tools and Performance Development in Sports Cardiology - Torun, Akın; Kılıç, Şahhan; Işık, Ömer (Galenos Publishing House, 2025)
Sports cardiology is a multidisciplinary field that has evolved to evaluate and optimize the cardiovascular health of athletes. The field focuses on improving exercise-related physical performance, reducing cardiovascular risks, and detecting potential diseases early. Sports cardiology monitors the heart health of athletes while also evaluating their cardiovascular responses during exercise. This process plays a critical role in increasing training intensity, managing fatigue, and preventing heart disease. In addition, one of the areas of interest of sports cardiology is performance medicine. A sports cardiologist and sports physician is a part of the athletic process from the athlete’s first examination to the final step of athletic success. Sports cardiology and performance medicine provide athletic and economic value to the sports industry by preventing injuries, objectively assessing performance, rapidly and effectively improving performance, and enhancing athletic success. In this review, we aim to present the assessment tools, and study areas of sports cardiology. ©Copyright 2025 by the Cardiovascular Academy Society.
Keywords: cardiorespiratory fitness; performance medicine; Sports cardiology